Knowledge, Attitudes and Practices of Menstrual Hygiene Management of Female Students in Bokkos Local Government Area of Plateau State; Nigeria - Gorah, Kajang Y.; Haruna, Elizabeth A.; Ufwil, Janda J. (NIU Journal of Social Sciences, 2020)
The study was carried out to help find the evaluation of the knowledge, attitudes and practices of female students towards menstrual hygiene management in Bokkos  local Government area of plateau state.  The survey research design was used for the study.  It is estimated that the number of children in the area of the study that are females are close to 3,000 out of this total, a sample size of 325 was used for the study.  A structured questionnaire of six sections was used to  illicit information on their level of knowledge, attitudes of female students towards menstrual hygiene, menstrual hygiene practices among female students, beliefs female students have towards menstrual hygiene, management strategies among female students and the health problems experienced among female students. The instrument was given to three experts in research, who are from the department of Physical and Health Education and one from test and measurement department of the faculty of Education University of Jos, whose inputs on the instrument was very helpful. It was pretested using respondents with similar characteristics to those in the area of the main study and a reliability co-efficient index of 0.76 was obtained, which was seem as a reliable figure for the instrument to be used for the present study. The public health educator, social workers, school authorities and parents should note the above findings and organize seminars and campaigns on menstrual hygiene management for female students in the area of study. The government should also provide restroom for ladies and enough water for their convenience. Knowledge, Attitudes,  Menstrual Hygiene , and Management of Female Students